2024
DOI: 10.15376/biores.19.2.2342-2352
|View full text |Cite
|
Sign up to set email alerts
|

Influence of densification on structural performance and failure mode of cross-laminated timber under bending load

Suman Pradhan,
Mostafa Mohammadabadi,
Edward D. Entsminger
et al.

Abstract: The effect of densification of the laminas was studied relative to the shear performance of cross-laminated timber (CLT) specimens submitted to the bending test. The three-layered CLT panels were fabricated using loblolly pine (Pinus taeda L.). A compression ratio (CR) of 50% was used to densify the lumber using the thermomechanical densification technique. The process included plasticizing the lumbers by soaking them in boiling water for 10 minutes and then hot-pressing to the target thickness at 140 °C. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…Given that the majority of densified specimens experienced tensile failure at the bottom layer, comprehensive analysis led to the determination that the developed bending stress (σ max ) corresponds to the bending strength (MOR) of the sample. This observed bending strength value averaged 47.45 MPa, closely aligning with the initial value reported by Pradhan et al [36]. This observation underscores the fact that the bending strength of CLT is predominantly governed by the bending strength of the bottom layer.…”
Section: Effect Of Densification On Failure Mode and Rolling Shear St...supporting
confidence: 90%
See 4 more Smart Citations
“…Given that the majority of densified specimens experienced tensile failure at the bottom layer, comprehensive analysis led to the determination that the developed bending stress (σ max ) corresponds to the bending strength (MOR) of the sample. This observed bending strength value averaged 47.45 MPa, closely aligning with the initial value reported by Pradhan et al [36]. This observation underscores the fact that the bending strength of CLT is predominantly governed by the bending strength of the bottom layer.…”
Section: Effect Of Densification On Failure Mode and Rolling Shear St...supporting
confidence: 90%
“…The findings clearly demonstrated that densification at 16.667% notably enhanced rolling shear strength, leading to a shift in the failure mechanism from rolling shear to tension. Similarly, in the study conducted by Pradhan et al [36], densification at 50% also induced a tension failure mode, restricting overall strength, primarily governed by the bending strength of the outer layer. However, densification at higher compression ratios would decrease the overall moment of inertia as higher densification is associated with a reduction in thickness, thereby impacting the bending stiffness of CLT.…”
Section: Effect Of Densification On Failure Mode and Rolling Shear St...mentioning
confidence: 68%
See 3 more Smart Citations